Relação entre a cinemática do retropé, tíbia e fêmur em corredores com e sem dor patelofemoral - Luz, Bruna Calazans (Universidade Federal de São Carlos, 2017)
Submitted by Aelson Maciera (aelsoncm@terra.com.br) on 2017-05-25T20:35:56Z No. of bitstreams: 1 DissBCL.pdf: 3021742 bytes, checksum: 521e476f6891dfc521177d5f7bd80228 (MD5) === Approved for entry into archive by Ronildo Prado (ronisp@ufscar.br) on 2017-05-30T14:07:29Z (GMT) No. of bitstreams: 1 DissBCL.pdf: 3021742 bytes, checksum: 521e476f6891dfc521177d5f7bd80228 (MD5) === Approved for entry into archive by Ronildo Prado (ronisp@ufscar.br) on 2017-05-30T14:07:41Z (GMT) No. of bitstreams: 1 DissBCL.pdf: 3021742 bytes, checksum: 521e476f6891dfc521177d5f7bd80228 (MD5) === Made available in DSpace on 2017-05-30T14:13:03Z (GMT). No. of bitstreams: 1 DissBCL.pdf: 3021742 bytes, checksum: 521e476f6891dfc521177d5f7bd80228 (MD5) Previous issue date: 2017-02-22 === Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) === Patellofemoral pain (PFP) is the most common running overuse injury. Excessive rearfoot eversion is commonly considered as a risk factor for patellofemoral pain and the relationship between the ankle-foot complex movement and the lower limb may be involved with this dysfunction. The purpose of this study was to evaluate the relationship between rearfoot eversion with tibia and femur kinematics in frontal and transverse planes during running in individuals with and without PFP. Methods: Fifty-four recreational runners were divided into 2 groups: healthy runners (CG, n = 27) and runners with patellofemoral pain (PFPG, n = 27). Kinematics during running were assessed using a three-dimensional motion analysis. Pearson's correlation coefficients (r) were calculated to establish the relationship of rearfoot eversion with tibial and femur movements (peak and range of motion). Findings: Greater peak rearfoot eversion was associated with greater peak tibial internal rotation and peak femur adduction in the PFPG. Additionally, greater peak rearfoot eversion was associated with greater femur adduction, femur external rotation and tibial adduction range of motion in the PFPG. Interpretation: Strongest associations between the greater rearfoot eversion and the greater peak hip adduction and hip adduction range of motion might be related to the etiology and/or persistence of patellofemoral pain, and indicate that treatment strategies aimed at controlling the movement of the rearfoot could help modify the symptoms. === A dor patelofemoral (DPF) é a lesão por sobrecarga mais comum da corrida. A eversão excessiva do retropé é comumente considerada como um fator de risco para a DPF e a relação entre o movimento do complexo do tornozelo-pé e do membro inferior pode estar envolvido com essa disfunção. O objetivo desse estudo foi avaliar a relação entre a eversão do retropé com a cinemática da tíbia e do fêmur nos planos frontal e transversal durante a corrida em individuos com e sem dor patelofemoral. Métodos: Cinquenta e quarto corredores recreacionais foram divididos em 2 grupos: corredores saudáveis (GC, n = 27) e corredores com dor patelofemoral (GDPF, n = 27). A cinemática durante a corrida foi avaliada por meio de um sistema de captura de movimento. Coeficiente de correlação de Pearson ( r ) foi calculado para estabelecer a relação da eversão do retropé com os movimentos da tíbia e do fêmur (pico e amplitude de movimento). Resultados: Um maior pico de eversão do retropé foi associado a um maior pico de rotação intera da tíbia e de adução do fêmur no GDPF. Além disso, um maior pico de eversão do retropé foi associado a uma maior amplitude de movimento de adução do fêmur, rotação externa do fêmur e adução da tíbia no GDPF. Interpretação: As associações mais fortes entre a maior eversão do retropé e o maior pico de adução do quadril e a amplitude de movimento de adução do quadril podem estar relacionadas à etiologia e/ou persistência da dor patelofemoral, e indicam que as estratégias de tratamento que visam controlar o movimento do retropé podem ajudar a modificar o sintomas.